The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/bjs.10991
|View full text |Cite
|
Sign up to set email alerts
|

Action observation for sensorimotor learning in surgery

Abstract: Background Acquiring new motor skills to learn complex movements and master the use of a diverse range of instruments is fundamental for developing expertise in surgery. Although aspects of skill development occur through trial and error, watching the performance of another individual (action observation) is an increasingly important adjunct for the acquisition of these complex skills before performing a procedure. The aim of this review was to examine the evidence in support of the use of action observation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…Before and after training, we also documented variable cortical activation in the different groups, both during the observation and execution of tasks. These data confirm that observing the actions of others is a cornerstone for the development of expertise and skilled behavior [16], and they support observational learning as an effective method for acquiring surgical skills [17]. Improved understanding of observational learning may further refine methods of surgical training.…”
Section: Discussionsupporting
confidence: 63%
“…Before and after training, we also documented variable cortical activation in the different groups, both during the observation and execution of tasks. These data confirm that observing the actions of others is a cornerstone for the development of expertise and skilled behavior [16], and they support observational learning as an effective method for acquiring surgical skills [17]. Improved understanding of observational learning may further refine methods of surgical training.…”
Section: Discussionsupporting
confidence: 63%
“…Observation and imitation are two crucial characteristics in medical skill education [ 18 ], and they have a variable influence on learning through format, content, and programming. The SDTM is derived from the terms and rules of the popular game called "spot the difference," which is a type of observational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, role modeling activities were stated as an important mentorship process in this study, since learners often learn by observing and imitating a role model. Evidence revealed that learning by observing and imitating others can be facilitated by mirror neuron`s activities in social contexts (55). Ramani (2003Ramani ( , 2008 and Carter (2016) explained that a clinical medical educator has the opportunity to be a role model to his learners and teach professional ethics and professionalism, performing procedures and conducting physical examinations without lecturing in a purely theoretical mode (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%